2020
DOI: 10.3390/foods9030358
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Flavonoid Compounds in Common Swedish Berry Species

Abstract: Berries are considered an ideal source of polyphenols, especially from the flavonoid group. In this study, we examined the flavonoid content in 16 varieties of Swedish lingonberry, raspberry, blueberry, and strawberry. Nineteen flavonoids were simultaneously quantified using external standards. An additional 29 flavonoids were tentatively identified using MS as no standards were available. Quantification was done using HPLC-UV after optimization of chromatographic and extraction procedures. The method showed h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 44 publications
(70 reference statements)
2
16
0
1
Order By: Relevance
“…In addition, fragments at m/z = 151 (C 7 H 3 O 4 − ) and m / z = 107 (C 6 H 3 O 2 − ) formed by the retro Diels–Alder reaction of quercetin moiety were also identified. Peak 18 with a m / z = 447.09341 was identified as quercitrin (C 21 H 19 O 11 − ) and showed a diagnostic fragment at m / z = 300.0275 due the loss of hexoside moiety, while peak 22 with a [M-H] − ion at m / z = 301.03561 was identified as quercetin aglycone [ 38 ]. Quercetin derivatives have been previously reported from G. phillyreifolia [ 11 ], G. poeppigii [ 11 ], G. mucronata [ 14 ], and G. antartica [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, fragments at m/z = 151 (C 7 H 3 O 4 − ) and m / z = 107 (C 6 H 3 O 2 − ) formed by the retro Diels–Alder reaction of quercetin moiety were also identified. Peak 18 with a m / z = 447.09341 was identified as quercitrin (C 21 H 19 O 11 − ) and showed a diagnostic fragment at m / z = 300.0275 due the loss of hexoside moiety, while peak 22 with a [M-H] − ion at m / z = 301.03561 was identified as quercetin aglycone [ 38 ]. Quercetin derivatives have been previously reported from G. phillyreifolia [ 11 ], G. poeppigii [ 11 ], G. mucronata [ 14 ], and G. antartica [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…Berries rich in polyphenolic compounds have shown promising effects in obesity-related metabolic adverse effects and low-grade inflammation in experimental models and in human studies [19][20][21]. Lingonberry is particularly rich in polyphenols and has a remarkable antioxidant activity; the most prevalent phenolic compounds in lingonberry are benzoic acid and its derivatives, flavanol oligomers (namely procyanidins), chlorogenic acid, quercetin derivatives and anthocyanins [22][23][24][25][26]. Recently, the authors of this study, and others, have reported that lingonberry supplementation has potential to inhibit high-fat diet-induced low-grade inflammation and adverse changes in glucose and lipid metabolism as well as visceral fat gain in a mouse model of obesity [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Acute intake of berries was only correlated with urinary (+)-catechin, whereas their habitual intake correlated with both urinary (+)-catechin and (-)-epicatechin and their sum. Berries are sources of flavan-3-ol monomers, especially (+)-catechin [34], which would explain the higher correlations observed between the urinary concentrations with this compound. Acute and habitual intake of chocolate and chocolate products was weakly correlated with urinary (-)-epicatechin.…”
Section: Discussionmentioning
confidence: 99%